The impact of geopolitical risks on the financial stability of the agricultural sector: a comparative analysis of Ukraine and the countries of the European Union - Kuzenko Tаtyana; Sablina Nataliіa; Voloschuk, Maksym; Glushkov, Oleg; Drugova, Olena; Sherstyuk, Oleksandr (Technology audit and production reserves, 2026)
The object of the research is the financial resilience of the agricultural sector in Ukraine and selected European Union (EU) countries under geopolitical and macroeconomic risks generating uncertainty in agribusiness. The problem addressed in the article lies in the absence of a unified methodological approach to the quantitative assessment of agricultural financial resilience under geopolitical risks, as well as limited comparability of results between Ukraine and EU countries. The findings indicate a statistically significant negative impact of geopolitical risks, currency volatility, and debt burden on the financial resilience of the agricultural sector. A persistent structural gap between Ukraine and EU countries has been identified: the average integral financial resilience index for Ukraine is approximately 0.38, compared to about 0.54 in EU countries. The patterns revealed in the study are explained by external risks affecting Ukraine’s agricultural sector. In contrast, higher financial resilience in EU countries is driven by a stable macroeconomic environment, diversified export structure, and institutional support mechanisms for agribusiness. A distinctive feature of the results is the integration of a balanced panel dataset with calculation of an integral financial resilience index based on normalized financial and institutional indicators. The practical application of the proposed index covers agricultural enterprises and financial management systems within the sector. The results are applicable under geopolitical risk conditions to assess financial resilience, evaluate risk impacts, and support informed managerial decisions.